Ectodomain shedding by ADAM17 increases the release of soluble CD40 from human endothelial cells under pro-inflammatory conditions - Klersy, Anton; Meyer, Sören; Leuschner, Florian; Kessler, Thorsten; Hecker, Markus; Wagner, Andreas H. (Cells, 2023)
Background: Homozygosity for the C allele of the −1T>C single nucleotide polymorphism (SNP) of the CD40 gene (rs1883832) is associated with susceptibility to coronary heart disease (CHD), enhanced CD40 expression, and shedding. The disintegrin metalloprotease ADAM17 can cleave various cell surface proteins. This study investigates an association between ADAM17-mediated CD40 shedding and inflammation in CC genotype human endothelial cells. Methods: Human umbilical vein endothelial cells (HUVEC) carrying the CC genotype were stimulated with soluble CD40 ligand (sCD40L) or tumor necrosis factor-α (TNFα). Messenger RNA and protein expression were determined with standard methods. Levels of high sensitive c-reactive protein (hs-CRP), interleukin-6 (IL-6), and sCD40 in plasma samples from patients with CHD were assessed using ELISA. Results: ADAM17 surface abundance was elevated following stimulation with CD40L and TNFα just as its regulator iRhom2. Inhibition of ADAM17 prevented TNFα-induced sCD40 and soluble vascular cell adhesion molecule-1 release into the conditioned medium and reinforced CD40 surface abundance. Secondary to inhibition of ADAM17, stimulation with CD40L or TNFα upregulated monocyte chemoattractant protein-1 mRNA and protein. Levels of sCD40 and the inflammatory biomarkers hs-CRP and IL-6 were positively correlated in the plasma of patients with CHD. Conclusions: We provide a mechanism by which membrane-bound CD40 is shed from the endothelial cell surface by ADAM17, boosting sCD40 formation and limiting downstream CD40 signaling. Soluble CD40 may represent a robust biomarker for CHD, especially in conjunction with homozygosity for the C allele of the −1T>C SNP of the CD40 gene.
Veröffentlicht: 25. Juli 2023
Gesehen am 02.10.2023